Gerakan Militan Islam Mesir dan Relevansinya dengan Politik Islam Indonesia: Studi Gerakan Ikhwan al-Muslimun - Khoiruddin Nasution (Universitas Islam Indonesia, 2000)
Ikhwanul Muslimin was a political movement which had brought a huge impact toward political changes in Egypt. Under Hassan Al-Banna's leadership, Ikhwanul Muslimin had brought a new atmosphere of competitions, especially in power struggle competition in Egypt. The efforts of Egyptian government to restrain and to conquer the movement had faced massive challenge and constant fight back as well. This article will bring its readers to understanding of Islamic political movements and it will also encourage them to be able to explore Islamic political movements and their dynamism.